Memori Verbal Sebagai Prediktor Kemampuan Bahasa Lisan Pada Anak-Anak Prasekolah - Yusi Lusia Ningsih; Rexsy Taruna (Politeknik Arutala Johana Hendarto [d.h. Akademi Terapi Wicara], 2023)
This study aims to assess how much the predictive power of verbal short term memory has on language skills. Participants in this study involved 50 typical preschool children, with a range of ages four to six years. Each participant was assessed using the Test of Auditory Processing Skill (TAPS-3) and Developmental Profile (DP-3). Data analysis in this study used correlation tests and linear regression tests with JASP. The results showed that there was a significant relationship between verbal short term memory and language skills (r = 0.635; p <0.001).